A publicidade de instituições bancárias e sua relação com o social: estudos da argumentação sob os olhares da semiótica e da retórica - Paula Silva Abreu (2021)
Studies on the construction of argumentation have been intensively carried out and reveal varied characteristics about human interaction through language. Based on these studies, this research aims to (i) explore advertisements from current and past banking institutions to identify how advertising benefits from social, cultural, historical changes in favor of persuasion; (ii) discuss the relationship between advertising and society, including reflections on the language and its functioning in the discussion and (iii) seek to understand how technological advances interfere and are, at the same time, added to advertising, promoting influences both in the structure as in the themes of the studied texts. For this, it is intended to develop a bibliographic review of concepts of Discursive Semiotics and Rhetoric, in order to have tools of interpretation and comparison of the pieces whose analysis allows to reach the proposed objectives. Authors such as Barros (2005), Fiorin (1995), Guedes (2014), Perelman and Tyteca (1996) and others can support the discussions to be undertaken when reflecting on: advertising in its persuasive nature, the ways in which argumentation and the epidemic genre are constructed as a publicity tool. In this way, it is observed, through a general and comparative reflection of the analysis of each piece, the changes in the ways of thinking and acting that happened in Brazil in the period between the 80s and today, with regard to the speeches that accompany the sphere of economics and banking institutions. Simultaneously to these reflections, this study also addresses the impacts of new digital technologies, which, as noted during the research, result in the transformation of the way of speaking and of the advertising itself, being, finally, the technological renewals responsible for modifying the interaction through language.